Antimicrobial activity of crude fractions and morel compounds from wild edible mushrooms of North western Himalaya. (April 2017) - Shameem, Nowsheen; Kamili, Azra N.; Ahmad, Mushtaq; Masoodi, F.A.; Parray, Javid A.
Abstract: The antimicrobial properties of morel compounds from wild edible mushrooms ( Morchella esculenta and Verpa bohemica ) from Kashmir valley was investigated against different clinical pathogens. The butanol crude fraction of most popular or true morel M. esculenta showed highest 19 mm IZD against E.coli while as same fraction of Verpa bohemica exhibited 15 mm IZD against same strain. The ethyl acetate and butanol crude fractions of both morels also exhibited good antifungal activity with highest IZD shown against A. fumigates. The three morel compounds showed quite impressive anti bacterial and fungal activities. The Cpd 3 showed highest inhibitory activity almost equivalent to the synthetic antibiotics used as control. The MIC/MBC values revealed the efficiency of isolated compounds against the pathogenic strains. In the current study significant inhibitory activity of morel compounds have been obtained paying the way for their local use from ancient times. Highlights: Verpa bohemica also showed an outstanding antibacterial activity against E.coli. Morel compounds exhibited effective antimicrobial activity against bacterial and fungal pathogens. Morel posses an enormous potential for nutraceuticals.